2017
DOI: 10.1186/s13041-017-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I alleviates motor and cognitive impairments via suppressing oxidative stress in the neonatal rats after hypoxic-ischemic brain damage

Abstract: Neonatal hypoxia-ischemia is one of the main reasons that cause neuronal damage and neonatal death. Several studies have shown that tanshinone I (TsI), one of the major ingredients of Danshen, exerts potential neuroprotective effect in adult mice exposed to permanent left cerebral ischemia. However, it is unclear whether administration of TsI has neuroprotective effect on neonatal hypoxic-ischemic brain damage (HIBD), and if so, the potential mechanisms also remain unclear. Here, we reported that treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 47 publications
2
27
1
Order By: Relevance
“…Here, a HI-induced reduction in GSH levels was observed in both injured groups, regardless AA treatment. HI-induced GSH decrease has been previously reported (Dai et al, 2017;Wu et al, 2017), however no effects of AA treatment was observed in this parameter. The discrepancies observed here and Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Here, a HI-induced reduction in GSH levels was observed in both injured groups, regardless AA treatment. HI-induced GSH decrease has been previously reported (Dai et al, 2017;Wu et al, 2017), however no effects of AA treatment was observed in this parameter. The discrepancies observed here and Fig.…”
Section: Discussionsupporting
confidence: 46%
“…Here, a HI‐induced reduction in GSH levels was observed in both injured groups, regardless AA treatment. HI‐induced GSH decrease has been previously reported (Dai et al, 2017; Wu et al, 2017), however no effects of AA treatment was observed in this parameter. The discrepancies observed here and the literature can be due to the stage of CNS maturation, since during neonatal period, glutamatergic neurons and transmission are not yet fully mature, and to the period of analysis, that is after the peak of injury induced glutamate release (Ben‐Ari, 2002; Brekke et al, 2015).…”
Section: Discussionmentioning
confidence: 49%
“…The Levine‐Rice model of neonatal HI provides a valuable experimental approach to reproduce the long term tissue brain damage and behavioral consequences of human hypoxia ischemia. HI rats show cognitive disabilities, with males being more susceptible to tissue loss in structure such as the CA1 area of hippocampus, a critical region for cognitive tasks (Arteni et al, 2010; Dai et al, 2017; Netto et al, 2017). Long‐term assessment of cognitive impairment, at 60 postnatal days and 90 postnatal days, has been reported after experimental neonatal HI (Arteaga et al, 2015; Sanches et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the impairment of learning and memory is the major sequelae of HIE in human and a variety of animal models of hypoxia (Dai et al, 2017). Long‐lasting cognitive consequences of neonatal hypoxia/HI include deficits in spatial learning and memory (Takada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in neuronal damage both in animal models of neonatal hypoxia and reoxygenation and in babies suffering from birth asphyxia (Caputa et al, 2005). An inhibition of oxidative stress may be a potential therapeutic for HIE (Dai et al, 2017; Zhang et al, 2018). It has been shown earlier that NADA exerts antioxidant and neuroprotective activities in different experimental models through mechanisms that are independent of CB1 and TRPV‐1 receptors (Bobrov et al, 2008; Grabiec et al, 2012; Novosadova et al, 2017).…”
Section: Discussionmentioning
confidence: 99%